A randomized trial of mexiletine in ALS: Safety and effects on muscle cramps and progression. (19th April 2016) - Weiss, Michael D.; Macklin, Eric A.; Simmons, Zachary; Knox, Angela S.; Greenblatt, David J.; Atassi, Nazem; Graves, Michael; Parziale, Nicholas; Salameh, Johnny S.; Quinn, Colin; Brown, Robert H.; Distad, Jane B.; et al.
Abstract : Objective: To determine the safety and tolerability of mexiletine in a phase II double-blind randomized controlled trial of sporadic amyotrophic lateral sclerosis (SALS). Methods: Sixty participants with SALS from 10 centers were randomized 1:1:1 to placebo, mexiletine 300 mg/d, or mexiletine 900 mg/d and followed for 12 weeks. The primary endpoints were safety and tolerability. Secondary endpoints were pharmacokinetic study from plasma and CSF, ALS Functional Rating Scale–Revised (ALSFRS-R) score, slow vital capacity (SVC), and muscle cramp frequency and severity. Results: The only serious adverse event among active arm participants was one episode of imbalance. Thirty-two percent of participants receiving 900 mg of mexiletine discontinued study drug vs 5% on placebo ( p = 0.026). Pharmacokinetic study demonstrated a peak plasma concentration 2 hours postdose and strong correlation between plasma and CSF ( p < 0.001). Rates of decline of ALSFRS-R and SVC did not differ from placebo. Analysis of all randomized patients demonstrated significant reductions of muscle cramp frequency (300 mg: rate = 31% of placebo, p = 0.047; 900 mg: 16% of placebo, p = 0.002) and cramp intensity (300 mg: mean = 45% of placebo, p = 0.08; 900 mg: 25% of placebo, p = 0.005). Conclusions: Mexiletine was safe at both doses and well-tolerated at 300 mg/d but adverse effects at 900 mg/d led to a high rate of discontinuation. Mexiletine treatment resulted in large dose-dependent reductions in muscle cramp frequency and severity. No effect on rate of progression was detected, but clinically important differences could not be excluded in this small and short-duration study. Classification of evidence: This study provides Class I evidence that mexiletine is safe when given daily to patients with amyotrophic lateral sclerosis at 300 and 900 mg and well-tolerated at the lower dose.